2006
DOI: 10.1128/ec.5.5.861-870.2006
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Mitochondrial Peroxiredoxin Prevents Programmed Cell Death inLeishmania donovani

Abstract: Leishmania promastigote cells transmitted by the insect vector get phagocytosed by macrophages and convert into the amastigote form. During development and transformation, the parasites are exposed to various concentrations of reactive oxygen species, which can induce programmed cell death (PCD). We show that a mitochondrial peroxiredoxin (LdmPrx) protects Leishmania donovani from PCD. Whereas this peroxiredoxin is restricted to the kinetoplast area in promastigotes, it covers the entire mitochondrion in amast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 60 publications
(73 reference statements)
1
29
0
2
Order By: Relevance
“…4 and 6). The intramitochondrial co-localization of a TXNPx isoform in C. fasciculata with the kDNA disk, in close proximity to UMSBP (41), similarly to its reported localization in L. infantum and L. major (35,43), is in accord with a potential functional role for TXNPx in kDNA metabolism, through its effect on the recognition of the kDNA minicircle replication origin.…”
Section: Discussionsupporting
confidence: 74%
“…4 and 6). The intramitochondrial co-localization of a TXNPx isoform in C. fasciculata with the kDNA disk, in close proximity to UMSBP (41), similarly to its reported localization in L. infantum and L. major (35,43), is in accord with a potential functional role for TXNPx in kDNA metabolism, through its effect on the recognition of the kDNA minicircle replication origin.…”
Section: Discussionsupporting
confidence: 74%
“…Several reports have shown that mitochondrial dysfunction or an imbalance of antioxidant homeostasis causes an increase in mitochondrion-generated ROS, which include H 2 O 2 , superoxide radical anions, singlet oxygen, and hydroxyl radicals. These species have all been implicated in apoptosis (16,26,28,41). Increasing evidence has been presented to support that ROS homeostasis regulates two major types of important physiological processes and exerts diverse functions within cells.…”
mentioning
confidence: 99%
“…Up-regulation of this protein has been associated with protection against apoptosis-like death (26) and resistance to miltefosine (27), a drug whose activity is linked to apoptosis and disturbance of lipiddependent cell signaling pathways (28). Moreover, Leishmania Prx1m confers thermotolerance to the parasite and displays in vitro chaperone activity, which seems to be crucial for virulence (29).…”
mentioning
confidence: 99%